1973
DOI: 10.1038/icb.1973.67
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corticosteroid on Absorption and Endogenous Production of Immunoglobulins in Calves

Abstract: An attempt was made to determine the efFect of corticosteroid on intestinal absorption and subsequent endogenous synthesis of immunoglobulins by the newborn calf. This was carried out by measuring changes in the serum concentration of IgGj, IgG2, IgM and IgA at intervals after birth in a total of 14 calves, 11 of which were born of corticosteroid-treated cows and the remainder from untreated cows. Calves were each fed 2 1 of a large volume of mixed colostrum in the first 6 hours after birth.The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 3 publications
2
10
0
1
Order By: Relevance
“…It was not clear (Muller et al 1975) if the impaired immunoglobulin absorption reported in calves (Husband et al 1973) was caused by the length of action of the corticosteroid used or by the immaturity of the calves at birth. The results presented here show that a single dose of a short-acting corticosteroid, given, on average, 2 days before parturition, produced the effect in relatively mature lambs born close to normal term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not clear (Muller et al 1975) if the impaired immunoglobulin absorption reported in calves (Husband et al 1973) was caused by the length of action of the corticosteroid used or by the immaturity of the calves at birth. The results presented here show that a single dose of a short-acting corticosteroid, given, on average, 2 days before parturition, produced the effect in relatively mature lambs born close to normal term.…”
Section: Discussionmentioning
confidence: 99%
“…Husband et al (1973) found that induction of calving with a long-acting corticosteroid inhibited the intestinal absorption of immunoglobulins in calves. In contrast, Muller et al (1975) found no effect of a short-acting corticosteroid (dexamethasone: DEX) on serum protein, or (1.-and y-globulin levels in calves at 3 days of age.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, unlike adult mice that generate markedly higher titers upon intranasal than oral vaccination with the Ad vectors (44), pups developed equivalent or higher titers upon oral application of the vaccines. This may be a reflection of the increased intestinal permeability of neonates (39,40), which facilitates uptake of macromolecules such as Abs, cytokines, and antibacterial factors present in breast milk. We reported formerly that the AdC68rab.gp vector given i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Vann et al (1995), studying the process of colostral antibodies absorption in calves, found an efficiency of 26% for IgG, 62% for IgM and 19% for IgA, in the first 6 hours of life. Husband et al (1972), Boyd & Boyd (1987) and Klobasa et al (1998) observed values between 42 and 46% for immunoglobulin G, when colostrum was consumed between two and seven hours post-partum. Higher values of absorption efficiency were found by Bush et al (1973) e Matte et al (1982), 66% and 65,8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the concentration of serum immunoglobulins declines in consequence of the catabolism and transference of the antibodies to different metabolic pools. The establishiment of endogenous production of IgG increases its concentration until normal levels are reached (Tennant et al, 1969;Bush et al, 1971;Husband et al, 1972;Ribeiro et al, 1983;Machado Neto & Packer, 1986;Baracat et al, 1997).…”
Section: Introductionmentioning
confidence: 99%